O-GlcNAcylation of eNOS in high-salt-induced thoracic aorta endothelial dysfunction in mice - Li, Chang; Gao, Liuming; Ling, Yi; Lv, Zhan (Frontiers in Pharmacology, 2025)
BackgroundExcessive salt intake is a well-established risk factor for hypertension. However, the molecular mechanisms by which salt-induced endothelial dysfunction contributes to blood pressure elevation remain incompletely understood.Methods and ResultsIn this study, mice were fed a normal-salt diet (NSD) or high-salt diet (HSD) for 4 weeks, and primary bovine aortic endothelial cells (BAECs) were treated with varying concentrations of NaCl. HSD mice showed increased diastolic blood pressure and impaired acetylcholine-induced vasodilation, while sodium nitroprusside responses remained intact. In vitro experiments further confirmed salt-induced vascular endothelial dysfunction, high NaCl treatment reduced the proliferation, migration, and tube formation abilities of BAECs. Western blot analysis revealed that high salt exposure significantly increased O-GlcNAc modification of eNOS and upregulated O-GlcNAc transferase (OGT) expression, without altering total eNOS protein levels. Notably, nitric oxide (NO) bioavailability was significantly reduced both in vivo and in vitro. Treatment with the OGT inhibitor OSMI-1 reversed these changes and restored endothelium-dependent relaxation in HSD mice.ConclusionOur findings suggest that high salt intake impairs endothelial function by enhancing O-GlcNAc of eNOS, thereby contributing to elevated diastolic blood pressure. The ability of OGT inhibition to reverse endothelial dysfunction highlights the therapeutic potential of targeting eNOS O-GlcNAc could be a promising approach for preventing salt-induced vascular damage and subsequent diastolic blood pressure elevation.